Morphology and surface treatment of fly ash from Pha Lai power plant - Thế, Ngô Kế (Vietnam Journal of Chemistry, 2012)
Puriﬁed ﬂy ash (FA) are suitable as polymer ﬁlling materials because of their density, good dispersity and ﬂuidity of globular particles. However, FA as a ﬁller has not been widely used up to now on account of low whiteness values and low friction of untreated FA surface. In order to improve the FA quality, a surface treating methods by HCl, NaOH and Ca(OH)2 solution are proposed in this paper. The results show that fly ash from Pha Lai power plant are good quality, smooth surface and strong, undestroyable in HCl solution. Chemical treatment by NaOH solution destroyed surface of fly ash and liberated smaller particle inside lead to rough surface. Specific surface area of modified fly ash increase 30 times and pore volume increase 40 times. Chemical treatment of fly ash with Ca(OH)2 resulted in rough surface and covered by small particle about   1 mm include calcium silicate and aluminate. The fly ash products from chemical treatment above can used as filler for polymer composite materials or modify with silane coupling agents.